SIR-B stereo-radargrammetry of Australia - Leberl, Franz; Mayr, W; Domik, Gitta; Kobrick, M (International journal of remote sensing)

Karl Eugen Müller (1865–1932) und seine Rolle in der Entwicklung der Algebra der Logik - Peckhaus, Volker (History and Philosophy of Logic)
Abstracts: The Philosopher's Index. Cumulative Edition 22 (1988), 509–510; Historical Abstracts 40A:4245. Rezensionen: Zbl. Math. 645.01019 (R. Murawski); MR 89e:01038 (Chris Brink).

Modellierung der dissipativen Eigenschaften linearer passiver Systeme unter Verwendung der Distributionentheorie - Böcker, Joachim

Generating Pattern Sequences for the Pseudo-Exhaustive Test of MOS-Circuits - Wunderlich, Hans-Joachim; Hellebrand, Sybille (18th International Symposium on Fault-Tolerant Computing, FTCS-18)

Integrated Tools for Automatic Design for Testability - Schmid, Detlef; Wunderlich, Hans-Joachim; Feldbusch, Fridtjof; Hellebrand, Sybille; Holzinger, Juergen; Kunzmann, Arno (Tool Integration and Design Environments, F.J. Rammig (Editor))

Automatisierung des Entwurfs vollständig testbarer Schaltungen - Hellebrand, Sybille; Wunderlich, Hans-Joachim (GI - 18. Jahrestagung II, Hamburg, 1988, Informatik-Fachberichte 188)

Magnetic-field-induced orientation of crystallites in powders of layered intercalation compounds detected by NMR - Halstead, Thomas K.; Schmidt, Claudia; Spiess, Hans W.; Schoellhorn, Robert; Mueller-Warmuth, Werner; Moeller, H. (The Journal of Physical Chemistry)
Keywords: Physical and Theoretical Chemistry; General Engineering

Deuteron two-dimensional exchange NMR in solids - Schmidt, Claudia; Blümich, B; Spiess, H.W (Journal of Magnetic Resonance (1969))
Keywords: General Engineering

Studium Arbeitslehre - Rückblick mit Ausblick - Bigga, Regine (Arbeitslehre / Polytechnik: Ein Beitrag zur Neuen Allgemeinbildung. Die Geschichte von Arbeit, Technik und Produktion im Unterricht)

Die Schleswig-Holsteinische Volkszeitung 1892 bis 1968 - Facetten aus ihrer Geschichte - Bigga, Regine; Danker, Uwe (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)